PENGARUH UKURAN KANTOR AKUNTAN PUBLIK, AUDIT FEE DAN PENGALAMAN AUDIT TERHADAP INDEPENDENSI AKUNTAN PUBLIK SERTA DAMPAKNYA TERHADAP KUALITAS AUDIT - Sasa S. Suratman (Indonesian Journal of Economics and Business, 2012)
This study aims to examine: (1) The relationship between the size of public accountant firm, audit fees and audit experience, (2) The effect of size of public accountant firm, audit fees and audit experience to the independence of public accountants and their impact on audit quality.This study uses a survey of 104 public accountant firms registered with Bapepam-LK as the unit of analysis, while the unit of observation is a partner or a manager or a senior auditor. This type of data is primary data collected by questionnaire. Testing the hypothesis by using Structural Equation Model (SEM).These results indicate that: (1) There is a relationship between the size of public accountant firm, audit fees, and audit experience, (2) the size of public accountant firm, audit fees and audit experience affect the independence of public accountants either simultaneously or partially , and (3) the size of public accountant firm, audit fees, audit experience, and independence of public accountants effect on audit quality either simultaneously or partially.